Cirrus cloud seeding has potential to cool climate. Issue 1 (15th January 2013) - Storelvmo, T.; Kristjansson, J. E.; Muri, H.; Pfeffer, M.; Barahona, D.; Nenes, A.
Abstract: Cirrus clouds, thin ice clouds in the upper troposphere, have a net warming effect on Earth's climate. Consequently, a reduction in cirrus cloud amount or optical thickness would cool the climate. Recent research indicates that by seeding cirrus clouds with particles that promote ice nucleation, their lifetimes and coverage could be reduced. We have tested this hypothesis in a global climate model with a state‐of‐the‐art representation of cirrus clouds and find that cirrus cloud seeding has the potential to cancel the entire warming caused by human activity from pre‐industrial times to present day. However, the desired effect is only obtained for seeding particle concentrations that lie within an optimal range. With lower than optimal particle concentrations, a seeding exercise would have no effect. Moreover, a higher than optimal concentration results in an over‐seeding that could have the deleterious effect of prolonging cirrus lifetime and contributing to global warming. Key Points: Cirrus seeding could potentially counter global warming Successful seeding requires improved knowledge of upper tropospheric conditions Premature implementation may have the opposite of desired effect